The Influence of KMS Trello on the Intern Performance CDC UIN Jakarta - Jihan Fadhilah; Evy Nurmiati (ULTIMATICS, 2022)
Trello is software used for knowledge and project management. The ease of appearance and integration with Google Drive makes the UIN Jakarta Career Center interested in using Trello as a workspace for their intern. The problem of this research stems from the number of internals with non-technological backgrounds and this is the first time using this tool. So the purpose of this study is to see the effect of Trello software on internal performance and to see the difference in influence between technology and non-technological internals by using a research method, namely a descriptive qualitative approach through interviews with several selected sources